O-prenylated 3-carboxycoumarins as a novel class of 15-LOX-1 inhibitors. - Atena Jabbari; Mina Mousavian; Seyed Mohamad Seyedi; Mehdi Bakavoli; Hamid Sadeghian (PLoS ONE)
Allyloxy, Isopentenyloxy, geranyloxy and farnesyloxy derivatives of 3-carboxycoumarin, at position 5, 6, 7, and 8, were synthesized and their inhibitory potency against human 15-lipoxygenase-1 (human 15-LOX-1) were determined. Among the synthetic coumarins, O-allyl and O-isopentenyl derivatives demonstrated no considerable lipoxygenase inhibition while O-geranyl and O-farnesyl derivatives demonstrated potent inhibitory activity. 5-farnesyloxy-3-carboxycoumarin demonstrated the most potent inhibitory activity by IC50 = 0.74 μM while 6-farnesyloxy-3-carboxycoumarin was the weakest inhibitor among farnesyl analogs (IC50 = 10.4 μM). Bonding affinity of the designed molecular structures toward 15-LOX-1 3D structure complexed with RS75091, as potent 15-LOX-1 inhibitor, was studied by utilizing docking analysis. There was a direct relationship between lipoxygenase inhibitory potency and prenyl length chain. The ability of the prenyl portion to fill the lipophilic pocket which is formed by Ile663, Ala404, Arg403, Ile400, Ile173 and Phe167 side chains can explain the observed relationship. Similarity rate between the docked models and complexed form of RS75091, from point of view of configuration and conformation, could explain inhibitory potency variation between each prenyloxy substitution of 3-carboxycoumarins.